Accelerating anaerobic digestion for methane production: Potential role of direct interspecies electron transfer. (July 2021) - Wang, Zixin; Wang, Tengfei; Si, Buchun; Watson, Jamison; Zhang, Yuanhui
Abstract: Anaerobic digestion is a commercial technology utilized to produce bioenergy from waste streams. However, anaerobic digestion suffers from inefficient interspecies electron transfer between syntrophic bacteria and methanogens, which limits its reaction rate and even leads to termination of the process. Direct interspecies electron transfer (DIET) has been recognized as a faster and more stable means to transport reducing equivalents between bacteria and archaea, demonstrating great potential to enhance the rate limiting steps during anaerobic digestion. The present paper reviews the DIET process with different mechanisms and related microbial syntrophic associations, discusses the role of DIET during the degradation of organics, investigates its start-up performance, and quantifies its methane production. Moreover, this paper aims to assess the design of an enhanced anaerobic process with DIET with respect to high-rate reactors, substrate stimulation, the effects of conductive materials, and its long-term operation, which has been rarely discussed before. The understanding of DIET is still in its infancy; thus, the present paper provides a comprehensive review on the whole process and points out the direction for its potential industrial application. Highlights: A systematic review of DIET during anaerobic digestion for methane production. Summarized mechanisms and related microbial syntrophic associations of DIET. Assessed roles of DIET in complex organic degradations under stressed conditions. Discussed design of enhanced anaerobic systems with DIET.